Contemporary American Memoirs in Action How to Do Things with Memoir - Danielewicz, Jane (American Literature Readings in the 21st Century, 2018)
This book analyzes a collection of literary memoirs to demonstrate how this genre is an avenue for participation in public life. Writers are repurposing the memoir, a genre known for its personal and expressive function, to engage in debate and serve political goals. The chapters provide case studies for memoir as social action that effects change by looking at the writing of Joan Didion, John Edgar Wideman, James McBride, M. Elaine Mar, Janisse Ray, Lucy Grealy, and Ann Patchett. Drawing on theories of genre and agency, Danielewicz asserts how these writers are acting pragmatically. Memoirs contribute to democratic society by offering solutions, creating new knowledge, revealing social trends, bringing issues to light, creating empathy and connection, and changing public opinion. .